2018
DOI: 10.1051/e3sconf/20184500054
|View full text |Cite
|
Sign up to set email alerts
|

The role of wastewater treatment plants in surface water contamination by plastic pollutants

Abstract: The aim of this paper was to review the literature data regarding the physico-chemical characteristic of plastic pollutants discharged with municipal sewage, the practical possibility of removing microplastic particles from wastewater during different treatment steps in WWTPs and the problem of surface water contamination within them. Microplastics (the size range of 1 nm to < 5 mm), have been recognized as an emerging threat, as well as an ecotoxicological and ecological risk for water ecosystems. Municipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Microplastics present in the aquatic environment reach it mainly from the land. They can be in the form of waste, which will become fragmented due to UV radiation, mechanical abrasion and biological degradation (Dris et al 2015b) or come from wastewater treatment plants (Mrowiec 2018) and are in the form of microbeads from cleansing gels or fibres from washing synthetic clothes (Lončarski et al 2018). It has been shown that washing machines can generate over 1,900 plastic fibres in the single cycle (Browne et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Microplastics present in the aquatic environment reach it mainly from the land. They can be in the form of waste, which will become fragmented due to UV radiation, mechanical abrasion and biological degradation (Dris et al 2015b) or come from wastewater treatment plants (Mrowiec 2018) and are in the form of microbeads from cleansing gels or fibres from washing synthetic clothes (Lončarski et al 2018). It has been shown that washing machines can generate over 1,900 plastic fibres in the single cycle (Browne et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To answer these questions, we collected samples above, within, and below the city of River Falls, the only city in the otherwise predominantly agricultural watershed. Because the potential for plastic particles to enter food webs increases with decreasing size (Mrowiec 2018), we used analytical methods that allowed for the detection of particles down to ~10 μm in length.…”
mentioning
confidence: 99%
“…In a case study Mrowiec (2018) , although municipal WWTPs are one of the primary sources of MPs in aquatic environment, most MP particles were removed through the primary treatment zones (e.g., solid skimming and sludge settling processes), followed by additional removal through tertiary treatment processes including membrane filtration and dissolved air flotation (DAF). However, due to a continuous intake of large volumes, even tertiary-level effluent may still contain a significant amount of MPs, along with smaller sizes (e.g., <20 μm) of MPs and MP fragments (e.g., NPs).…”
Section: Evaluation Of Membrane Filtration For the Removal Of Micropl...mentioning
confidence: 99%